Regional Economic Outlook, April 2007, Sub-Saharan African. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2007)
Sub-Saharan Africa's growth performance during the past three years has been the best in more than three decades, and higher oil revenues and increased debt relief have been used to make progress toward the Millennium Development Goals (MDGs). Despite spending pressures, most countries have managed to preserve macroeconomic stability with policies intended to support and sustain the region's higher growth. This latest REO is complemented by analyses on the macroeconomic challenges for oil producers, the changing trade patterns, including with China, and the development of government debt markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet